Intermediasi Perbankan Syariah pada Bank Syariah Mandiri Cabang Jambi - Habriyanto Habriyanto (NALAR FIQH: Jurnal Hukum Islam, 2011)
This article discusses about intermediation of bank sharia Mandiri Jambi. The main study to see how much third party funding and financing by bank sharia Mandiri Jambi and development bank intermediation. Based on the finding of the field turn out third party fund and financing has increased and growth. It is influenced by factors such as costumer motive in accordance with the beliefs and economics motive. Sources of financing at a bank in equity and third party fund but if the bank are not sufficient to do financing, so the bank will recourse to other branch office or use equity owner of bank. Monthly Intermediation level of bank sharia Mandiri Jambi have significant enhancer. The highest increase occurred in August 2006 at 141,31%. This is influenced by the increase of 36,71% musharaka financing. Intermediation level based on annual data are generally, the highest percentage occurred in 2007at 130, 71% because of musharaka financing increase amount 183,63%. Intermediation level of bank sharia Mandiri Jambi indicate that the bank had perform its function as regulator of Islamic financial. With the increase of financing by that bank will economic development community and can assist local authorities to develop local economy.